Cardiovascular biomarkers in patients with COVID-19 - Müller, Christian; Giannitsis, Evangelos; Jaffe, Allan S; Huber, Kurt; Mair, Johannes; Cullen, Louise; Hammarsten, Ola; Mills, Nicholas L; Möckel, Martin; Krychtiuk, Konstantin; Thygesen, Kristian; Lindahl, Bertil (European heart journal - acute cardiovascular care, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has increased awareness that severe acute respiratory distress syndrome coronavirus-2 (SARS-CoV-2) may have profound effects on the cardiovascular system. COVID-19 often affects patients with pre-existing cardiac disease, and may trigger acute respiratory distress syndrome (ARDS), venous thromboembolism (VTE), acute myocardial infarction (AMI), and acute heart failure (AHF). However, as COVID-19 is primarily a respiratory infectious disease, there remain substantial uncertainty and controversy whether and how cardiovascular biomarkers should be used in patients with suspected COVID-19. To help clinicians understand the possible value as well as the most appropriate interpretation of cardiovascular biomarkers in COVID-19, it is important to highlight that recent findings regarding the prognostic role of cardiovascular biomarkers in patients hospitalized with COVID-19 are similar to those obtained in studies for pneumonia and ARDS in general. Cardiovascular biomarkers reflecting pathophysiological processes involved in COVID-19/pneumonia and its complications have a role evaluating disease severity, cardiac involvement, and risk of death in COVID-19 as well as in pneumonias caused by other pathogens. First, cardiomyocyte injury, as quantified by cardiac troponin concentrations, and haemodynamic cardiac stress, as quantified by natriuretic peptide concentrations, may occur in COVID-19 as in other pneumonias. The level of those biomarkers correlates with disease severity and mortality. Interpretation of cardiac troponin and natriuretic peptide concentrations as quantitative variables may aid in risk stratification in COVID-19/pneumonia and also will ensure that these biomarkers maintain high diagnostic accuracy for AMI and AHF. Second, activated coagulation as quantified by D-dimers seems more prominent in COVID-19 as in other pneumonias. Due to the central role of endothelitis and VTE in COVID-19, serial measurements of D-dimers may help physicians in the selection of patients for VTE imaging and the intensification of the level of anticoagulation from prophylactic to slightly higher or even therapeutic doses.